Faktor-faktor yang mempengaruhi opini audit going concern - Edwina Putri Pertiwi; Yuni Nustini (Proceeding of National Conference on Accounting & Finance, 2023)
The purpose of this study is to analyze the relationship between profitability, company size, company growth, leverage, audit lag, audit tenure, debt default, financial distress and opinion shopping towards going concern audit opinion in manufacturing companies listedion Indonesia Stock Exchange (IDX) during the period of 2019-2021. In this study, the data used is the secondary data from annual reports that contains any informations needed this study and it use purposive sampling method to get the data. This study use profitability (ROA), company size (Ln. Total Assets), company growth (Tota Assets Ratio), leverage (DER), audit lag (the difference between the date of the financial statement and the audit report), audit tenure (how long time KAP cooperation with company), debt default (dummy variable), financial distress (Revised Altman bankruptcy) and opinion shopping (dummy variable) as independent variable and going concern audit opinion (dummy variable) as dependent variable. This study used 57 companies out from 513 total population. This study use binary logistic regression analysis method for data processing and analyzing. The results of this study show that profitability has a negative effect on going concern audit opinion. Audit lag, debt default and opinion shopping have a positive effect on going concern audit opinion. Company size, company growth, leverage, audit tenure and financial distress have no effect on going concern audit opinion.